The effect of women directors on innovation activity and performance of corporate firms: Evidence from China - Marina Töpfer (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
This paper elaborates whether women bringing their diversity, cross-cultural awareness and transformational leadership skills to corporate boards offer strategic advantages for firms. In the analysis the effect of women in the board room on innovation activity and corporate firm performance as well as the joint consequences of female directors and innovation activity on the firm's success are examined. The latter may be particularly important in the context of gender diversity as more gender-diverse boards allow for higher levels of creativity and hence innovation. In order to account for endogeneity issues, different model specifications are employed (two-way fixed effects models and linear dynamic panel data models). Unconditional quantile regressions are used in order to go beyond the mean. The analysis is conducted using Chinese firm-level data from 2006-2015. The results suggest positive effects of gender diversity in corporate boards and patenting activities on firm performance. Women directors are found to have statistically significant effects on both input-(positive) and output-oriented (negative) innovation activity.
urn:nbn:de:bsz:100-opus-15034
Keywords: G30; J16; 330; Women Directors; Innovation Activity; Firm Performance; Gender-diverse Boards; Unconditional Quantile Regression